MEDIA RELATIONS AS AN INTEGRAL PART OF COMMUNICATION STRATEGY - Ermamatova, Kumushbibi; doktori, Filologiya fanlari bo‘yicha falsafa; sharqshunoslik, Toshkent davlat (Research Focus International Scientific Journal, 2026)
This article analyzes effective media relations of organizations and companies as an important component of communication strategy. It discusses the development of media cooperation strategies, building relationships with journalists, providing valuable information organizing media events, using social networks, managing reputation, and analyzing results.